Interaction of Electromagnetic and in Conductors and its Utilization - Cap, Ivo; Capova, Klara; Faktorova, Dagmar (Communications - Scientific letters of the University of Zilina, 2003)
The paper deals with the interaction of electromagnetic and acoustic processes in a conducting medium in presence of an external magnetic field. The electromagnetic excitation of acoustic wave similarly as acoustic excitation of electromagnetic wave is described. The practical utilization consisting in contactless acoustic wave generation and detection is demonstrated.